KORELASI RAGAM AKTIVITAS TERHADAP KEBERHASILAN MAKAN TIGA JENIS KUNTUL DI CAGAR ALAM PULAU DUA TELUK BANTEN, SERANG (Makara Journal of Science, 2008)
Correlation in Activity Variation to Feeding Success on Three Species Herons at Pulau Dua Nature Reserve Banten's Bays, Serang. This research intent to know activity manner influence that did by three species herons for feeding success at Pulau Dua Nature Reserve, Banten Bay, Serang. Observational method that is utilized is direct observing with backed up by picture taking utilizes observation method is focal. Analysis draws to be done by scan sampling method's. Data analyzed by correlation terminologically Spearmann by programs SPSS. Result observationally to point out that activity type was done upon eating is step, strike, catch and devours prey. Result tests Spearmann's correlation proves that activity manner a large part gets positive correlation with feeding success for three species herons depend on different feeding location. Just activity stop and not active just that gets negative correlation with feeding success on three species herons